The Big Big Big Book of Tashi : Seven Books in One - Fienberg, Anna ; Barbara; Illustrated by Kim Gamble (Australia Allen & Unwin, 2001)
He's brave! He's bold! HE'S THE BEST! Tashi's too cunning for the war lord and the wicked baron, and far too clever for giants, ghosts, witches and demons. Seven books are rolled into one big book of Tashi with 14 stories. Ages 6-10.
Include illustrations
Keywords: Tashi (Fictitious character) -- Children's stories, Australian -- Australia